(untitled) (Journal of Asian Development Studies, 2023)
This study aimed to investigate the effectiveness of Eidetic therapy in reducing guilt and shame proneness in individuals with cannabis addiction. The inclusion criteria maintained the usage for less than 2 years without psychotic features, with mild, moderate, and severe levels of drug abuse. Purposive sampling techniques were used to approach a population of 25 participants from different cities in Pakistan. The sample was assessed using the Drug Abuse Screening Test (Skinner, 1982), the Positive and Negative Syndrome Scale (Opler, 1987), and the Guilt and Shame Proneness Scale (Cohen, 2011). A sample of three participants who scored high, moderate, and low, respectively, on the DAST and GASPS scale were selected for the intervention phase and received eidetic therapy as an intervention. Post-treatment testing was done, and it concluded a significant reduction in the usage of drugs and guilt and shame proneness. The data was analyzed using a paired sample T-test. This study provides promising insights into the effectiveness of Eidetic psychotherapy as a therapeutic intervention, highlighting its potential to significantly reduce both drug addiction and the associated guilt and shame proneness in individuals with cannabis use disorder without psychotic features, as well as be helpful if repeated with a different population in future